Association between recent oncologic treatment and mortality among patients with carcinoma who are hospitalized with COVID‐19: A multicenter study. Issue 3 (2nd November 2020) - Song, Kehan; Gong, Hongyun; Xu, Bin; Dong, Xiaorong; Li, Linjun; Hu, Weidong; Wang, Qun; Xie, Zhibin; Rao, Zhiguo; Luo, Zhiguo; Chu, Qian; Li, Feng; et al.
Abstract : Background: To the authors' knowledge, little is known regarding the association between recent oncologic treatment and mortality in patients with cancer who are infected with coronavirus disease 2019 (COVID‐19). The objective of the current study was to determine whether recent oncologic treatment is associated with a higher risk of death among patients with carcinoma who are hospitalized with COVID‐19. Methods: Data regarding 248 consecutive patients with carcinoma who were hospitalized with COVID‐19 were collected retrospectively from 33 hospitals in Hubei Province, China, from January 1, 2020, to March 25, 2020. The follow‐up cutoff date was July 22, 2020. Univariable and multivariable logistic regression analyses were performed to identify variables associated with a higher risk of death. Results: Of the 248 patients enrolled, the median age was 63 years and 128 patients (52%) were male. On admission, 147 patients (59%) did not undergo recent oncologic treatment, whereas 32 patients (13%), 25 patients (10%), 12 patients (5%), and 10 patients (4%), respectively, underwent chemotherapy, surgery, targeted therapy, and radiotherapy. At the time of last follow‐up, 51 patients (21%) were critically ill during hospitalization, 40 of whom had died. Compared with patients without receipt of recent oncologic treatment, the mortality rate of patients who recently received oncologic treatment was significantly higher (24.8% vs 10.2%; hazard ratio, 2.010 [95% CI, 1.079‐3.747; P = .027]). After controlling for confounders, recent receipt of chemotherapy (odds ratio [OR], 7.495; 95% CI, 1.398‐34.187 [ P = .015]), surgery (OR, 8.239; 95% CI, 1.637‐41.955 [ P = .012]), and radiotherapy (OR, 15.213; 95% CI, 2.091‐110.691 [ P = .007]) were identified as independently associated with a higher risk of death. Conclusions: The results of the current study demonstrated a possible association between recent receipt of oncologic treatment and a higher risk of death among patients with carcinoma who are hospitalized with COVID‐19. Abstract : The current study demonstrates a possible association between receipt of recent oncologic treatment and a higher risk of death among patients with carcinoma who are hospitalized with COVID‐19. Therefore, particular attention should be given to COVID‐19–infected patients who have undergone recent oncologic treatment.